PENERAPAN TERAPI RELAKSASI AUTOGENIC TERHADAP PENURUNAN INSOMNIA PADA PASIEN HIPERTENSI DI KOTA SEMARANG - Krisma Prihatini; Ns. Ainnur Rahmanti (Pusat Riset dan Inovasi Nasional, 2021)
Hypertension is a condition where systolic blood pressure is equal to or more than 140 mmHg and diastolic blood pressure is more than or equal to 90 mmHg. The cause of hypertension can be influenced by genetic factors, environmental factors or influenced by a combination of these two factors. From the causative factors, hypertension can be classified into 2, namely: primary or essential hypertension for which the cause is not known, and secondary hypertension which is hypertension arising from other diseases. According to the American Heart Association in 2019, there were about 4 billion people on the Asian continent, but levels of awareness, treatment and blood pressure control tend to be low. The Chinese population has a presentation of 47% of the population who are aware and check themselves for hypertension, 14% of whom are undergoing treatment. Singapore has 74% of people aware of hypertension and 69% undergoing treatment. In America, about 46% of adults have hypertension, about 40% of whom are African-American-non-Hispanic men and women. Women aged 20 to 34 years, 13% had hypertension; nearly 86% of the condition was in their mid-70s. Men at that age also had the same condition, increasing from about 26% to 80%.